Development of a Codular-Based Instructional Media for Vocabulary Material at High School: Taṭwīr Wasīlah Ta’līmiyyah Mabniyyah ‘alā Codular-Based Instructional li Mawād al-Mufradāt fī al-Madrasah al-‘Āliyah - Dinata, Prima Yoga; Amiruddin, Amiruddin; Muslim, Ahmad Bukhari; Aridan, Muhammad (Study Program of Arabic Language Teaching, 2023)
This research aims to develop, validate, and measure the effectiveness of the Quadolar-based Arabic language teaching method in teaching vocabulary to tenth-grade students. The study adopts the Hannafin and Peck research model, which consists of needs analysis, design, development, and implementation phases. Involving subject matter experts and method experts as assessors, this study uses pre-test and post-test data analyzed with a t-test. The research results indicate the successful development of the Quadolar-based teaching method, with excellent quality according to subject matter and method experts. Individual trials, small-group, and large-group experiments also indicate a positive level of acceptance of this method. Its effectiveness is evidenced by a learning outcome difference of 38.75, with t-test results showing a high level of significance (t-score 62.5 vs. t-table 2.093). Therefore, this research concludes that the Quadolar-based Arabic language teaching method is a worthwhile and effective approach to teaching Arabic in this environment.